WAJAH PURITANISME DALAM DRAMA MOURNING BECOMES ELECTRA KARYA EUGENE O’NEILL - Fajar Setiawan Roekminto (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
It’s impossible to discuss American literature without mentioning Eugene O’Neill, including his renowned drama Mourning Becomes Electra (MBE). MBE is a drama that describes a Puritan family called the Mannons. The main characters in MBE live in a strict and severe Puritan society. Both the Mannons and Puritans establish a family and community on the same principles, the belief in covenant, a tenet that is taught by John Calvin. They also have the same dream about a new land, New Jerusalem for Puritans and Blessed Island for the Mannons. The article aims at disclosing the constricting Puritans society in New England and the cruelty of the central characters in MBE. In addition, the way in which Eugene O’Neill creates tragic characters at the end of the drama can be related to the decline of Puritanism. Goldmann’s sociology of literature is applied as an approach. The imaginary structure between an aesthetic and history—MBE and Puritan society—is discovered. The Mannons in MBE and Puritans in New England have similar attitudes. Both are cruel because they desire to be in power and control economic fields. The efforts to realize the dreams are challenged by other communities and it marks the beginning of puritanical decline in New England and the death of central character in MBE. The tragic visions of the Mannons and puritans guide them to death and fall.